Large Pyoderma Gangrenosum-Like Ulcers: A Rare Presentation of Granulomatosis with Polyangiitis. (18th May 2014) - Tashtoush, Basheer; Memarpour, Roya; Johnston, Yasmin; Ramirez, Jose
Abstract : Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis (WG), is a rare systemic vasculitis that classically manifests as necrotizing granulomas of the upper and lower respiratory tract, kidneys, and blood vessels; however, it may affect any organ system, including the skin. Cutaneous manifestations occur in up to 45% of patients during the disease course, and are the presenting feature in 9% to 14% of patients. The most common skin lesion specific to GPA is palpable purpura, with the histopathologic correlate of leukocytoclastic vasculitis. However, a wide range of clinical and histologic features may be seen. We herein report a case of a previously healthy 52-year-old Caucasian man who presented with multiple progressively enlarging painful ulcers on his face, upper extremities, back, and abdomen over a two-month period. Skin biopsies revealed pyoderma gangrenosum-like features. Serological tests were positive for PR3/c-ANCA. Six months later, the patient developed recurrent episodes of sinusitis associated with nasal bleeds and eventually nasal septum perforation. Despite aggressive treatment with Cyclophosphamide and steroids over one year, the patient had persistent nonhealing large ulcers and developed multiple lung nodules with cavitary lesions.